2018
DOI: 10.1038/s41591-018-0028-4
|View full text |Cite
|
Sign up to set email alerts
|

The reference epigenome and regulatory chromatin landscape of chronic lymphocytic leukemia

Abstract: Chronic lymphocytic leukemia (CLL) is a frequent hematological neoplasm in which underlying epigenetic alterations are only partially understood. Here, we analyze the reference epigenome of seven primary CLLs and the regulatory chromatin landscape of 107 primary cases in the context of normal B cell differentiation. We identify that the CLL chromatin landscape is largely influenced by distinct dynamics during normal B cell maturation. Beyond this, we define extensive catalogues of regulatory elements de novo r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
233
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(249 citation statements)
references
References 79 publications
(114 reference statements)
15
233
0
1
Order By: Relevance
“…From our chromatin feature maps, we derived a highly connected CLL‐specific network centered around the TFs targeting 17 central binding motifs and an enrichment of BCR signaling genes (Fig B and C, Appendix Fig S7 and Table S2, Dataset EV14). These central motifs include gained motifs in CLL for NFAT, TCF4, and LEF1 and lost motifs for EBF1 and AP‐1, which have similarly been reported in two other studies (Oakes et al , ; Beekman et al , ). The integrated view on the interplay of TFs, chromatin modifiers, and associated target genes derived here provides a rich resource to generate hypotheses for novel molecular links to the CLL pathophenotype.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…From our chromatin feature maps, we derived a highly connected CLL‐specific network centered around the TFs targeting 17 central binding motifs and an enrichment of BCR signaling genes (Fig B and C, Appendix Fig S7 and Table S2, Dataset EV14). These central motifs include gained motifs in CLL for NFAT, TCF4, and LEF1 and lost motifs for EBF1 and AP‐1, which have similarly been reported in two other studies (Oakes et al , ; Beekman et al , ). The integrated view on the interplay of TFs, chromatin modifiers, and associated target genes derived here provides a rich resource to generate hypotheses for novel molecular links to the CLL pathophenotype.…”
Section: Discussionsupporting
confidence: 73%
“…Accordingly, we envision that the approach of developing integrated gene regulatory enhancer containing networks will prove to be valuable for therapy response prediction and patient stratification for CLL. Furthermore, the comprehensive data sets created here and in another study (Beekman et al , ) provide a rich resource for CLL researchers. It will largely facilitate studies that involve clinically relevant disease phenotypes with deregulated molecular mechanisms, which are reflected by the multitude of aberrant features present in the CLL epigenome.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Whole-exome sequencing studies have identified recurrent somatic mutations in coding regions of a number of genes including TP53, SF3B1, NOTCH1, and MYD88, as well as significant inter- and intra-tumoral heterogeneity (Landau et al, 2013; 2015). Whole-genome analysis of 150 CLL samples revealed disrupted gene regulatory sites in distal enhancers of the PAX5 locus (Puente et al, 2015), and a very recent study from the same group profiled the epigenomic features of a large CLL cohort and panel of normal B cell subtypes, revealing dysregulated enhancers in CLL subtypes including IGHV -M and IGHV -U cases (Beekman et al, 2018). Another cohort of CLL samples has also recently been assessed by ATAC-seq, revealing subtype-specific open chromatin signatures of CLL (Rendeiro et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding annotation was performed by intersection with sites of expected non-coding functionality in CLL. Functional non-coding sites were determined as follows: the region must be within a peak of ATAC-seq activity in 20% of CLL samples (>21/106) fromBeekman et al (2018) 47 .Additionally, the region must be identified as either active promotor, strong enhancer1, or strong enhancer2 by CHROMHMM48 in 3 or more samples including 7 CLL and a further 15 from various blood cells (2x csMBC, 1x ncsMBC, 3x GCBC, 3x NBCB, 3x NBCT and 3x PCT). Briefly, CHROMHMM was used to combine 6 histone modification marks in each CLL sample to identify genomic functionally active regions, as described in Beekman et al (2018) 47 .…”
mentioning
confidence: 99%